A Simple Forecasting Accuracy Criterion Under Rational Expectations : Evidence From the World Economic Outlook and Time Series Models - Barrionuevo, Jose (IMF Working Papers; Working Paper ;, 1992)
A simple criterion based on the properties of the forecast error is presented to evaluate the accuracy of forecasts. The efficiency conditions of an optimization problem are used to show that under rational expectations the standard statistical conditions are necessary, but not sufficient to ensure efficiency. This criterion is used to examine the accuracy of the World Economic Outlook projections of growth and inflation for the seven major industrial countries. Time series models are then estimated and the efficiency of the World Economic Outlook projections relative to a benchmark time series model is examined. A number of empirical tests suggest that the year ahead projections of growth and inflation in the World Economic Outlook are unbiased after 1982.